Optimization of the use of smartphones in the implementation of implementers in teaching and learning - Harianto, Dedek; Matesa Br Ginting, Loficha; Putra Bintang, Dandi; Jamaludin, Jamaludin; Yunita, Sri (Lembaga Penelitian dan Pendidikan Mandala, 2023)
The use of smartphones in the teaching and learning process can be optimized by utilizing various features and applications available on the device. According to some studies, smartphones can be used as a source of learning materials, interactive learning media, and a tool to access e-books and online learning platforms. The use of smartphones can also make learning more fun and less boring. However, there are also some challenges in using smartphones for teaching and learning, such as the need for a stable internet connection and potential distractions. To optimize the use of smartphones in the teaching and learning process, it is important to establish clear guidelines and policies, provide training for teachers and students, and continuously evaluate the effectiveness of the approach.with Qualitative research method a research method based on positivist philosophy, used to consider the current state of the subject. The problem was studied with quantitative methods by interviewing teachers at Smk Pab 3 school, the researcher conveyed that all data submitted through interviews to teachers were only used for the purpose of this study, and examined how a teacher's implementation of smartphone optimization in the classroom to realize effective optimization. The identity of the overall teacher is kept confidential and matters relating to the teacher's response to the interview because the research data is confidential.